Ease of market entry of Indian startups: formal and informal institutional influences - Scillitoe, Joanne L.; Birasnav, Muthuraj (South Asian Journal of Business Studies, 2021)
Purpose The purpose of this study offers a theoretical model, hypotheses and empirical analyses of how formal and informal institutions influence the ease of market entry of startups in the context of India. Design/methodology/approach A theoretical model based upon institutional and market entry theories is presented with hypotheses. Structural equation modeling is used to test the hypotheses. Findings Results of the study suggest that college preparations and a culture of creativity and innovation are positively related to ease of market entry by Indian startups. A culture of personal success is negatively related to ease of market entry. Government assistance related to ease of market entry is not significant. Originality/value This paper offers a new perspective, linking formal and informal institutional influences to startup ease of market entry. In addition, informal institutions are viewed from the cultures of personal success and creativity/innovation within the entrepreneurial domain, which is also new to the literature. This paper offers specific insights in the context of India startups and offers some interesting findings that can contribution to the literature, policy and practice.
Keywords: Culture; Entrepreneurship; India; Institutions; Market entry; Startup; dept.mgt; peer-reviewed